2021
DOI: 10.3389/fcimb.2021.711144
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect of Streptococcus pyogenes-Released Extracellular Vesicles on Human Monocytic Cells, Induction of Cytotoxicity, and Inflammatory Response

Abstract: Most bacteria naturally release spherical lipid-bilayered extracellular vesicles (EVs) containing proteins, nucleic acids, and virulence-related molecules, thus contributing to diverse biological functions including transport of virulence factors. The group A streptococcus, Streptococcus pyogenes (GAS), a major human pathogen, also releases EVs; however, it remains unclear how GAS EVs interact physiologically and pathologically with host cells, and what the differences are between invasive and non-invasive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The study of gram-positive bacteria-derived vesicles is rapidly expanding and suggests a newfound pathogenicity of oral bacterial infection. Recently, various reports disclosed that MVs from gram-positive bacteria enclosed many virulence-related proteins such as streptolysin O and NAD-glycohydrolase in Streptococcus pyogenesis [45] and lipoproteins in Staphylococcus aureus [46] and Streptococcus pneumoniae [47]. MVs play roles in intercellular communication involving biofilm formation, nutrition acquisition and quorum sensing [9,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The study of gram-positive bacteria-derived vesicles is rapidly expanding and suggests a newfound pathogenicity of oral bacterial infection. Recently, various reports disclosed that MVs from gram-positive bacteria enclosed many virulence-related proteins such as streptolysin O and NAD-glycohydrolase in Streptococcus pyogenesis [45] and lipoproteins in Staphylococcus aureus [46] and Streptococcus pneumoniae [47]. MVs play roles in intercellular communication involving biofilm formation, nutrition acquisition and quorum sensing [9,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…EMV production has been reported in S . pyogenes [ 22 25 ]. It is negatively regulated by the CovRS, a two-component system that controls the expression of 15% of S .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the averaged diameter of 103 + -EVs (130 nm) is slightly bigger than 103 − -EVs (105 nm) ( Figure 1 ). The size of EVs in Gram-positive bacterial varies between different bacterial strains [ 34 , 35 , 36 , 37 ], throughout various stages of bacterial growth [ 38 ], and environmental conditions [ 27 , 39 , 40 ]. As the reports that the size distribution of EVs of the invasive Streptococcus pyogenes strains SSI-1 were 1.31 times bigger than the non-invasive Streptococcus pyogenes strains JRS4 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The size of EVs in Gram-positive bacterial varies between different bacterial strains [ 34 , 35 , 36 , 37 ], throughout various stages of bacterial growth [ 38 ], and environmental conditions [ 27 , 39 , 40 ]. As the reports that the size distribution of EVs of the invasive Streptococcus pyogenes strains SSI-1 were 1.31 times bigger than the non-invasive Streptococcus pyogenes strains JRS4 [ 37 ]. The bigger size of EVs means it can carry more active molecules including virulence factor.…”
Section: Discussionmentioning
confidence: 99%